2021
DOI: 10.3390/ijerph18010276
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ABO Blood Grouping on COVID-19 Vulnerability and Seriousness: A Retrospective Cross-Sectional Controlled Study among the Arab Community

Abstract: Background and Objectives: Studies have noted that some ABO blood types are more susceptible to COVID-19 virus infection. This study aimed to further confirm the relationship between different blood groups on the vulnerability, symptoms, cure period, and severity among COVID-19 recovered patients. Subjects and Methods: This cross-sectional study approached the participants from the Arab community via social media (mainly Facebook and WhatsApp). The data were collected through two Google Form questionnaires, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 56 publications
3
19
0
Order By: Relevance
“…A recent study found that myalgia was significantly lower among the patients with blood type AB. 32 Similar to the findings of Hoiland et al, 33 the current study discovered that WBC count was higher in patients with blood group A. Peak S. ferritin was also significantly higher in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A recent study found that myalgia was significantly lower among the patients with blood type AB. 32 Similar to the findings of Hoiland et al, 33 the current study discovered that WBC count was higher in patients with blood group A. Peak S. ferritin was also significantly higher in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Though to our knowledge, very few studies have tried to find this kind of relationship; in one study, COVID-19-infected patients having blood groups AB or A had a higher percentage of the requirement for mechanical ventilation, 33 while in another study, the blood group O showed the highest rate requiring artificial respiration. 32 One possible explanation for these disparate findings is that the latter one of these studies has failed to account for different confounding variables, including comorbidities. Another potential confounding factor is the inclusion of randomly chosen voluntary blood donors for controls, given the chance of group O demographic prevalence resulting from blood collectors collecting group O donors selectively.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin levels also increase [109]. While many studies have shown that COVID-19 causes significant changes in ALT and AST levels and decreases albumin levels [110], according to studies, it seems that because Numerous studies confirm the change in ALT and AST levels. ALT and AST levels affect the course of COVID-19 disease.…”
Section: Am J Biomed Sci and Resmentioning
confidence: 97%
“…According to the inclusion criteria, we excluded the 216 irrelevant studies by screening abstract and title. Eventually, a total of 22 articles (GÖKER et al, 2020;Hoiland et al, 2020;Ad'hiah et al, 2020;Solmaz and Araç, 2021;Taha et al, 2020;Dzik et al, 2020;Zalba et al, 2020;Chegni et al, 2020;Franchini et al, 2021;Gamal et al, 2021;Wu et al, 2020;Khalil et al, 2020;El-Shitany et al, 2021;Valenti et al, 2020;Muñiz-Diaz et al, 2021;Kibler et al, 2020;Barnkob et al, 2020;Bhandari et al, 2020;Rahim et al, 2021;Abdollahi et al, 2020;Fan et al, 2020;Boudin et al, 2020) were included in this systematic review and meta-analysis (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%